Differential Impact of the Pinewood Nematode on Pinus Species Under Drought Conditions - Estorninho, Mariana; Chozas, Sergio; Mendes, Angela; Colwell, Filipe; Abrantes, Isabel; Fonseca, Luís; Fernandes, Patrícia; Costa, Catarina; Máguas, Cristina; Correia, Otília; Antunes, Cristina (Frontiers in Plant Science, 2022)
The pinewood nematode (PWN), Bursaphelenchus xylophilus, responsible for the pine wilt disease (PWD), is a major threat to pine forests worldwide. Since forest mortality due to PWN might be exacerbated by climate, the concerns regarding PWD in the Mediterranean region are further emphasized by the projected scenarios of more drought events and higher temperatures. In this context, it is essential to better understand the pine species vulnerability to PWN under these conditions. To achieve that, physiological responses and wilting symptoms were monitored in artificially inoculated Pinus pinaster, P. pinea, and P. radiata saplings under controlled temperature (25ºC/30ºC) and water availability (watered/ water stressed). The results obtained showed that the impact of PWN is species-dependent, being infected P. pinaster and P. radiata more prone to physiological and morphological damage than P. pinea. For the more susceptible species (P. pinaster and P. radiata), the presence of the nematode was the main driver of photosynthetic responses, regardless of their temperature or water regime conditions. Nevertheless, water potential revealed to be highly affected by the synergy of PWN and the studied abiotic conditions, with higher temperatures (P. pinaster) or water limitation (P. radiata) increasing the impact of nematodes on trees’ water status. Furthermore, water limitation had an influence on nematodes density and its allocation on trees’ structures, with P. pinaster revealing the highest nematode abundance and inner dispersion. In inoculated P. pinea individuals, nematodes’ population decreased significantly, emphasizing this species resistance to PWN. Our findings revealed a synergistic impact of PWN infection and stressful environmental conditions, particularly on the water status of P. pinaster and P. radiata, triggering disease symptoms and mortality of these species. Our results suggest that predicted drought conditions might facilitate the impact of PWN on these two species, through xylem cavitation, leading to strong changes in pine forests of the Mediterranean regions.